2015
DOI: 10.14227/dt220415p38
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dissolution Profiles of Commercially Available Lamivudine Tablets

Abstract: The aim of this study was to investigate the influence of dissolution medium on the in vitro release of lamivudine (100 mg) from four commercially available lamivudine tablets (one reference and three generic). Three different buffer solutions (pH 1.2, 4.5, 6.8) and deaerated water were used as the dissolution media (900 mL), and the paddle rotation speed was kept at 50 rpm with twelve replicates. An RP-HPLC method was developed for analysis of lamivudine in samples obtained from dissolution studies. The mobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
1
4
0
1
Order By: Relevance
“…4, both drugs complied with the requirement for products exhibiting very rapid dissolution, namely, more than 85% of the drugs were dissolved within 15 minutes in all three buffers (WHO, 2017). Similar results were reported by (Ozturk et al, 2015;Reddy et al, 2014;Strauch et al, 2011). The intermediate precision analysis at all sampling times, showed RSD values below 7% for both drugs, demonstrating the intermediate precision of the method.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…4, both drugs complied with the requirement for products exhibiting very rapid dissolution, namely, more than 85% of the drugs were dissolved within 15 minutes in all three buffers (WHO, 2017). Similar results were reported by (Ozturk et al, 2015;Reddy et al, 2014;Strauch et al, 2011). The intermediate precision analysis at all sampling times, showed RSD values below 7% for both drugs, demonstrating the intermediate precision of the method.…”
Section: Resultssupporting
confidence: 86%
“…In the British Pharmacopoeia, the methods provided use ultraviolet spectrophotometry at 280 nm and 266 nm, for lamivudine and zidovudine, respectively (BP, 2018a;2018b). Some published works have reported methods of quantification of lamivudine and zidovudine tablets in dissolution studies through UV spectrophotometric and HPLC (Fernandes et al, 2003;Hwisa et al, 2013;Mandloi et al, 2009;Ozturk et al, 2015;Stuart et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The dissolution test is an important tool in drug development and quality control studies for tablet formulations. It is also used to design new formulations, develop in vitro-in vivo correlations, control in-process and finished product specifications, show the similarity of pharmaceutical dosage forms, and evaluate the bioequivalence of reference and generic products (11,12). Permeability is the rate-limiting step in the oral absorption of BCS Class 3 compounds such as MH (13).…”
mentioning
confidence: 99%
“…Regarding the dissolution profiles, our results agree with the study conducted in Turkey by Otzurk et al . which obtained more than 85% of the labeled amount dissolved in 15 min in the three-dissolution media: pH 1.2 (97.5%, 100.0% and 99.9%); pH 4.5 (96.4%, 101.0% and 99.8%); and pH 6.8 (103.0%, 98.8% and 100.0%); therefore, the mathematical comparison of similarity (f2) was not necessary either 17 . On the contrary, a study carried out in Argentina showed that the results obtained for LMV and abacavir presented an f2 greater than 50 for the three generic lots for both LMV and abacavir at pH 1.2 and 6.8; however, for pH 4.5, lot 1 did not meet f2 for either of the two actives 18 .…”
Section: Discussionmentioning
confidence: 99%